Efficacy of Azithromycin for Preventing Chronic Lung Disease of Prematurity: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Obieda Altobaishat; Elsayed Balbaa; Moumen Arnaout; Hashem Alsaid Ahmad; Husam Abu Suilik; Abdulrahman Sharaf; Zaid Bataineh; Mohamed Abouzid (Current Pharmacology Reports, 2026)

Ferric Carboxymaltose Among Patients with Heart Failure and Iron Deficiency: An Updated Meta-Analysis of Randomized Controlled Trials - Ahmed Elmorsy Mohamed; Ahmed Farid Gadelmawla; Zeyad Kholeif; Elsayed Balbaa; Ameer Awashra; Mohamed Elnady; Ahmed Diaa; Mohab Elnashar; Haytham A. M. Dwaik; Eman Mohyeldin; Ranem Afify; Rana Rashwan; et al. (Cardiovascular Toxicology, 2026)

Protamine sulphate for heparin reversal in percutaneous cardiac interventions: a systematic review and meta-analysis of randomized controlled trials - Elsayed Balbaa; Ahmed Farid Gadelmawla; Abdelrahman M. Tawfik; Ahmed Naeem; Ahmed Elbataa; Mohammad Bazzazeh; Ahmed Ramadan Fatiem; Khaled Ali; Obieda Altobaishat; Mohamed Abuelazm (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)
Vascular complications after percutaneous cardiac interventions are a significant cause of morbidity that affects post-procedural prognosis. Data about the efficacy and safety of routine protamine sulphate to prevent these complications remain scarce. Hence, we aim to assess the efficacy and safety of routine protamine sulphate use for heparin reversal in patients undergoing percutaneous cardiac interventions. We systematically searched PubMed, Embase, Cochrane, Scopus, and Web of Science for randomized controlled trials (RCTs) until September 2024. The RCTs’ quality was assessed using the Cochrane tool (RoB 2). Using R, we pooled dichotomous outcomes using risk ratios (RR) and continuous outcomes using mean differences (MD), both along the corresponding 95% Confidence interval (CI). PROSPERO ID: (CRD42024593002). Six RCTs with 1,076 patients were eligible. Hemostasis success was significantly higher in the protamine group (RR, 1.06; 95% CI [1.01–1.10]; P = 0.01), and the length of hospital stay was significantly shorter (MD, -0.46; 95% CI [-0.65, -0.26]; P < 0.01). There was no significant difference between both groups in stroke (RR, 0.60; 95% CI [0.18–2.03]; P = 0.41), major bleeding ( P = 0.25), minor bleeding ( P = 0.11), life-threatening bleeding ( P = 0.65), time to ambulation ( P = 0.13), all-cause mortality ( P = 0.92), hematoma/pseudoaneurysm ( P = 0.92), and major vascular complications ( P = 0.70). While protamine improved hemostasis success, its effect on reducing bleeding events and time to ambulation was insignificant. Also, reducing the length of hospital stay in the protamine group highlights its potential clinical benefit. Graphical Abstract

Efficacy and safety of colchicine post myocardial infarction: a systematic review, meta-analysis and meta-regression analysis of randomized clinical trials - Farhan Naeem; Shehroze Tabassum; Muhammad Burhan; Elsayed Balbaa; Ahmed Ibrahim; Shrouk Ramadan; Usama Qamar; Fatima Saeed; Mohamed Abuelazm; Dmitry Abramov; Timir K. Paul; Yasar Sattar (European Journal of Clinical Pharmacology, 2025)

Serum Copper Levels in Chronic Kidney Disease and Hemodialysis Patients: Insights from a Systematic Review and Meta-Analysis - Abdullah Yousef Aldalati; Ayham Mohammad Hussein; Elsayed Balbaa; Bassel Alrabadi; Moath Albliwi; Mohammad Abuassi; Badi Rawashdeh (Biological Trace Element Research, 2025)

Detection of New Point Mutations of BRCA1 and BRCA2 in Breast Cancer Patients - Moufida Bensam; Elsayed Hafez; Doaa Awad; Muhammad El-Saadani; Mahmoud Balbaa (Biochemical Genetics, 2014)